Co-dirección cortometraje: Pato - Navarrete Cedeño, Esteban Andrés (2016)
The following undergraduate thesis, CODIRECTION OF THE SHORT FILM PATO consists of producing a film and elaborating a supporting theoretical writing. The main objective is to achieve an own filmic language through the guidance of the work of other filmmakers. This short film is supported by a theoretical work on the concept of postmodernism that articulates bibliographic and inematographic sources in order to analyze its characteristics in relation to the movie Pato. As a result of this analysis and the production of the film we developed a new language based on previous cinematographic references.